Oil prices in a real-business-cycle model with precautionary demand for oil - Conny Olovsson (Sveriges Riksbank, 2016)
This paper analyzes the interaction between oil prices and macroeconomic outcomes by incorporating oil as an input in production alongside a precautionary motive for holding oil in a real-business-cycle model. The driving forces are factor-specific technology shocks and supply shocks that can be imprecisely forecasted by noisy news shock. These shocks explain most of the U.S. business cycle as well as the empirical distribution of oil prices. Oil shocks are mainly driven by increasing precautionary/smoothing demand, but supply shocks contribute substantially to both the oil-price volatility and the magnitude of oil shocks mainly through their effect on oil reserves.
Keywords: E32; Q43; 330; Oil price shocks; business cycles